2023
DOI: 10.3390/life13122242
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum 8-Iso-Prostaglandin F2α as an Oxidative Stress Marker and Immunological Markers in a Cohort of Preeclampsia Patients

Lidia Boldeanu,
Constantin-Cristian Văduva,
Daniel Cosmin Caragea
et al.

Abstract: Background: We aimed to analyze the presence and clinical use of serum 8-iso-prostaglandin F2-alpha (8-iso-PGF2α) as an oxidative stress marker and some inflammatory status biomarkers (tumor necrosis factor-alpha (TNF-α), interleukin 6 (IL-6), IL-10, high-sensitivity C-reactive protein (hs-CRP), and pentraxin-3 (PTX3)) for patients with preeclampsia (PE). Methods: Sixty pregnant women, including thirty diagnosed with PE and thirty who were healthy (NP), were included in this study. For the assessment of serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…On the other hand, if we refer to the study of the dynamics of 8-epi-PGF2α during pregnancy, in which measurements should be made at least twice for this marker of oxidative stress, we did not find published studies. In a previously published study [37], in the second trimester of pregnancy and in the postpartum period (three months after delivery), we assessed 8-epi-PGF2α in patients with PE compared to pregnant women without PE. Our preliminary study showed that the expression levels of serum 8-iso-PGF2α in the PE group were higher than that in the PE after-delivery group.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, if we refer to the study of the dynamics of 8-epi-PGF2α during pregnancy, in which measurements should be made at least twice for this marker of oxidative stress, we did not find published studies. In a previously published study [37], in the second trimester of pregnancy and in the postpartum period (three months after delivery), we assessed 8-epi-PGF2α in patients with PE compared to pregnant women without PE. Our preliminary study showed that the expression levels of serum 8-iso-PGF2α in the PE group were higher than that in the PE after-delivery group.…”
Section: Introductionmentioning
confidence: 99%